2018
DOI: 10.1080/00224545.2017.1412932
|View full text |Cite|
|
Sign up to set email alerts
|

Gun attitudes on campus: United and divided by safety needs

Abstract: All people share a need for safety. Yet people's pursuit of safety can conflict when it comes to guns, with some people perceiving guns as a means to safety and others perceiving guns as a threat to safety. We examined this conflict on a U.S. college campus that prohibits guns. We distinguished between people (N = 11,390) who (1) own a gun for protection, (2) own a gun exclusively for reasons other than protection (e.g., collecting, sports), and (3) do not own a gun. Protection owners felt less safe on campus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 19 publications
6
40
0
Order By: Relevance
“…Importantly, non-protection gun owners more closely resembled non-gun owners than protection gun owners. The conclusion was that gun ownership alone was not a reliable predictor of either an individual's feelings of safety on campus or of his or her support for campus carry legislation (Shepperd et al, 2017).…”
Section: Quantitative Surveysmentioning
confidence: 92%
See 4 more Smart Citations
“…Importantly, non-protection gun owners more closely resembled non-gun owners than protection gun owners. The conclusion was that gun ownership alone was not a reliable predictor of either an individual's feelings of safety on campus or of his or her support for campus carry legislation (Shepperd et al, 2017).…”
Section: Quantitative Surveysmentioning
confidence: 92%
“…IHEs regarding campus carry legislation. As discussed above, several previous studies of campus carry, some conducted in Florida, found that a majority of the students, faculty, and staff at IHEs opposed campus carry and believed that allowing guns on campus would have a deleterious effect on the learning environment (Bartula & Bowen, 2015;Bennet, Kraft, & Grubb, 2012;Canon, 2016: Cavanaugh, Bouffard, Wells, & Nobles, 2012Patten, Thomas, & Wada, 2013;Shepperd et al, 2017;Shepperd et al, 2018;Spratt, 2015;Thompson, et al, 2013;Webster et al, 2016). The results of this survey study are unlikely to differ significantly from those of previous studies; the aim here was rather to reveal the specific point of view of campus public safety directors in Florida, a population that has not been targeted in previous surveys.…”
Section: Assumptionsmentioning
confidence: 99%
See 3 more Smart Citations